Evaluasi Kinerja Linear Search, Binary Search, dan SQL Query pada Sistem Informasi Berbasis Web - Sri Shinta Wahyuni Hidayat; Anita Andriani; Aries Dwi Indriyanti; Edwin Hari Agus Prastyo (TIN: Terapan Informatika Nusantara, 2026)
Data management in educational information systems requires efficient search mechanisms to provide fast and accurate access to information. Although various search algorithms have been widely implemented in web-based information systems, studies comparing application-level search algorithms with database-level search mechanisms that utilize query optimization features remain limited. This study aims to design and develop a web-based student data management information system and evaluate the performance of Linear Search, Binary Search, and SQL Query methods in data retrieval processes. The system was developed using the Laravel framework and MySQL database through the Waterfall approach, consisting of requirements analysis, system design, implementation, and testing stages. Performance testing was conducted using 1,000 student records with search scenarios based on Student Identification Numbers (NIS). The evaluation focused on measuring search execution time under the same testing environment for each method. The results showed that SQL Query achieved the best performance with an average execution time of 0.0065 seconds, outperforming Binary Search at 0.0248 seconds and Linear Search at 0.0369 seconds. These findings indicate that database indexing and query optimization mechanisms can significantly improve search efficiency compared to application-level search algorithms. However, the results are limited to a dataset of 1,000 records and cannot yet be generalized to large-scale data environments. This study contributes empirical evidence regarding the performance characteristics of different search methods in web-based information systems and provides practical insights for selecting appropriate data retrieval strategies.